Biomimetic osteogenic peptide with mussel adhesion and osteoimmunomodulatory functions to ameliorate interfacial osseointegration under chronic inflammation. (October 2020) - Bai, Jiaxiang; Wang, Huaiyu; Chen, Hao; Ge, Gaoran; Wang, Miao; Gao, Ang; Tong, Liping; Xu, Yaozeng; Yang, Huiling; Pan, Guoqing; Chu, Paul K.; Geng, Dechun
Abstract: Bone endoprosthesis in patients with systemic chronic inflammation frequently leads to poor osseointegration after implantation mainly due to the increase in pro-inflammatory cytokines that induce bone resorption and impair bone formation. In this work, peptide-coated implants are designed to create a beneficial bone immune microenvironment around prostheses to promote interfacial osteogenesis. By taking advantage of the spontaneous and stable coordination chemistry, Ti-based implants are coated with the mussel-inspired peptide to mitigate lipopolysaccharide (LPS)-induced inflammation by up-regulating the M2 phenotype of macrophages. In addition, the peptide coating increases the bone-implant contact (BIC) by nearly 3 times resulting in suppressed osteoclastogenesis and promoted osteogenesis by inhibiting the nuclear factor kappa-B (NF-κB) signalling pathway. Our findings indicate that biomimetic peptides with osteoimmunomodulatory bioactivity can be incorporated into Ti-based prostheses to facilitate bone regeneration in patients with chronic inflammatory diseases. Graphical abstract: A biomimetically designed peptide with mussel adhesion and osteogenic properties is synthesized for regulation of interfacial osteoclasts and osteoblasts under inflammatory conditions. The peptide-coated implants reduce inflammation and change the macrophages to M2 phenotype in lipopolysaccharide (LPS)-caused systemic inflammatory diseases consequently suppressing osteoclastogenesis and promoting interfacial osteogenesis and osseointegration after implantation. Image 1 Highlights: A mussel-inspired peptide coating with titanium affinity is developed. The peptide coating downregulates the inflammatory response of M1 macrophages. The peptide coating promotes osteogenesis and inhibits osteoclastogenesis. The peptide coating improves interfacial osseointegration.